Constructive Side-Channel Analysis and Secure Design: 6th International Workshop, COSADE 2015, Berlin, Germany, April 13-14, 2015. Revised Selected Papers - Mangard, Stefan; Poschmann, Axel Y (LNCS sublibrary. SL 4, Security and cryptology, 2015)
This book constitutes the thoroughly refereed post-conference proceedings of the 6th International Workshop, COSADE 2015, held in Berlin, Germany, in April 2015. The 17 revised full papers presented were carefully selected from 48 submissions. the focus of this workshop was on following topics: side-channel attacks, FPGA countermeasures, timing attacks and countermeasures, fault attacks, countermeasures, and Hands-on Side-channel analysis.